Studies on new substituted pyridazinones: synthesis and biological evaluation - Mohammad Asif; Anita Singh; Shah Alam Khan; Asif Husain (Universidade de São Paulo, 2018)
We report herein the synthesis and pharmacological evaluation of a new series of 6-aryl-2-(imidazol-1-yl/1,2,4-triazol-1-yl)-2-methyl-4,5-dihydro-(2H)-pyridazin-3-one (3a-j) as potential anticonvulsant and antitubercular agents. The title compounds were prepared by reacting 6-aryl-4,5-dihydro-(2H)-pyridazin-3-one (2a-e) with formaldehyde and secondary cyclic amine imidazole or 1,2,4-triazole as per Mannich reaction. Anticonvulsant activity of pyridazinone derivatives was tested at 50 mg.kg-1 dose level against maximal electroshock (MES), isoniazid (INH, 250 mg.kg-1) and pentylenetetrazole (PTZ at 80 mg.kg-1) induced seizure methods. Phenytoin sodium (25 mg.kg-1) and sodium valproate (100 mg.kg-1) were used as reference drugs for comparison purpose. In-vitro antitubercular activity was tested by Microplate Alamar Blue assay (MABA) method and the results were compared with clinically used antitubercular agents such as INH, Pyrazinamide (PZA) and Streptomycin (STM). None of the screened compounds were found to be neurotoxic at a dose level of 100 mg.kg-1. All the screened compounds (3a-j) significantly reduced the MES, INH and PTZ induced convulsions and thus showed good anticonvulsant activity. The minimum inhibitory concentration (MIC) of the title compounds against M. tuberculosis ranged from 1.6 µg/mL to 6.25 µg/mL in comparison to INH, PZA (3.125 µg/mL) and STM (6.25 µg/mL) which indicated good antitubercular activity.